Ethnic foods of Northeast India: insight into the light of food safety - Madhuchhanda Das; Anup Kumar Ojha; Pallab Sarmah; Dimpu Gogoi; Karma G. Dolma; Tapan Majumdar; Suranjana Chaliha Hazarika; Dilem Modi; Goutam Chowdhury; Chaitali Konwar; Reema Nath; Samaresh Das; et al. (BMC, 2024)
Abstract Background Traditional and fermented foods are widely consumed by the ethnic population of Northeast India. These foods are not only very nutritious, easily available, and reasonably priced, but also boost immunity and protect from various seasonal infections and have been reported through several investigations. However, pathogens transmitted by these foods have never been reported. The process of preparation and preservation of fermented traditional foods involves various steps that can prompt contamination risks. Using the Indian Council of Medical Research (ICMR)-FoodNet surveillance data, we report the profile of enteric bacteria and mycotoxin-producing fungal pathogens identified in traditional and fermented food items and their importance in public health. Methods Food samples were collected from rural areas of Assam, Arunachal Pradesh, Tripura, and Sikkim. Bacterial and fungal pathogens were tested as per the standard operating procedure at respective ICMR-FoodNet laboratories and MycoNet laboratory at Assam. Samples were collected under six broad categories: milk products, edible insects, non-vegetarian, legumes/cereals, veggies, and alcoholic beverages. Data compilation was done centrally through a digital data portal. Quality assurance was done by the ICMR-National Institute for Research in Bacterial Infections (NIRBI), Kolkata. Result A total of 1227 samples were collected, among which 78 samples (6.8%) were positive for enteric pathogens, with Bacillus cereus being the most prevalent one (n = 59). Furthermore, 71 fungal isolates were detected from different food categories. The most common mycotoxin-producing fungal genera include Aspergillus [A. fumigatus (n = 7)], Rhizopus [R. arrhizus (n = 13)], and Penicillium (n = 2). Conclusion Traditional foods have immense social, and cultural value and popularity among locals. However, processing, fermentation, and preservation of these foods without any preservatives and refrigerators, increases the possibility of contamination and growth by pathogenic organisms. It is crucial to understand the contamination risk involved during preparation so that the safety of these traditional foods can be ensured and local delicacies can be relished without any fear of foodborne infections and outbreaks, particularly when consumed by masses during festivals.